On the Optimization of the IEEE 802.11 DCF: A Cross-Layer Perspective - Massimiliano Laddomada; Fabio Mesiti (International Journal of Digital Multimedia Broadcasting)
This paper is focused on the problem of optimizing the aggregate throughput of the distributed coordination function (DCF) employing the basic access mechanism at the data link layer of IEEE 802.11 protocols. We consider general operating conditions accounting for both nonsaturated and saturated traffic in the presence of transmission channel errors, as exemplified by the packet error rate 𝑃𝑒. The main clue of this work stems from the relation that links the aggregate throughput of the network to the packet rate 𝜆 of the contending stations. In particular, we show that the aggregate throughput 𝑆(𝜆) presents two clearly distinct operating regions that depend on the actual value of the packet rate 𝜆 with respect to a critical value 𝜆𝑐, theoretically derived in this work. The behavior of 𝑆(𝜆) paves the way to a cross-layer optimization algorithm, which proved to be effective for maximizing the aggregate throughput in a variety of network operating conditions. A nice consequence of the proposed optimization framework relies on the fact that the aggregate throughput can be predicted quite accurately with a simple, yet effective, closed-form expression. Finally, theoretical and simulation results are presented in order to unveil, as well as verify, the key ideas.